The Level of Ca125 in Preand Postoperative of Endometriosis - Amsir, Asriyanti; Tahir, Andi M; Abdullah, Nusratuddin (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To determine the Ca-125 level in pre- and post-operative of endometriosis and its correlation to endometriosis stage and severity of dysmenorrhea. Method: This was a cross-sectional study design conducted at Dr. Wahidin Sudirohusodo dan some affiliated hospitals. We took the patients undergoing laparoscopy or laparotomy consecutively. Result: The mean value of preoperative Ca-125 level in stage I-II was 21.53 (SD 12.64) IU/ml vs 72.52 (SD 8.52) IU/ml in stage III-IV. The mean value of postoperative Ca-125 level was 14.82 (SD 10.00) IU/ml (stage I-II) vs 61.03 (SD 8.43) IU/ml (stage III-IV); they were significantly different (p